Skin-to-Skin Care and Rooming-In: Safety Considerations. Issue 2 (March 2017) - Killion, Molly M.
Abstract : New recommendations from the American Academy of Pediatrics about safety considerations during skin to skin in the first few hours of life and rooming in practices for new mothers and babies during the postpartum inpatient stay are discussed.